Host-feeding preference of Phlebotomus orientalis (Diptera: Psychodidae) in an endemic focus of visceral leishmaniasis in northern Ethiopia - Araya Gebresilassie; Ibrahim Abbasi; Essayas Aklilu; Solomon Yared; Oscar David Kirstein; Aviad Moncaz; Habte Tekie; Meshesha Balkew; Alon Warburg; Asrat Hailu; Teshome Gebre-Michael (Parasites & Vectors, 2015)
Abstract Background Blood-feeding behavior studies are important for estimating the efficiency of pathogen transmission and assessing the relative human disease risk. However, in Ethiopia and other parts of East Africa there are large remaining gaps in identifying the feeding habits of Phlebotomus orientalis, the vector of Leishmania donovani. The aim of the study was to determine the blood feeding patterns of P. orientalis in Tahtay Adiyabo district, northern Ethiopia. Methods For bloodmeal analysis, sandflies were collected from three different villages of Tahtay Adiyabo district using CDC light traps, sticky traps, and pyrethrum spray catches. Bloodmeal of engorged female sandflies was identified using cytochrome (cyt) b-PCR and reverse-line blotting (RLB) and enzyme linked immunosorbent assay (ELISA) assays. Results Most (637/641) of the females analyzed were P. orientalis. Successful identification of the host from bloodmeals was achieved in 83.03 and 92.1 % using cyt b PCR-RLB and ELISA, respectively. Bloodmeal analysis of P. orientalis females revealed that they have a range of hosts with predominant preference to bovines followed by donkey, human, goat, sheep, dog, and camel. Conclusion Results obtained from bloodmeal analyses demonstrate that the feeding preference of P. orientalis is mainly zoophilic, which could vary depending on the availability of hosts.